Bob Marley, one love [videorecording (Blu-Ray)] - Green, Reinaldo Marcus, 1981-; Winter, Terence; Flowers, Frank E.; Baylin, Zach, 1980-; Ben-Adir, Kingsley; Lynch, Lashana, 1987-; Norton, James, 1985-; Cole, Tosin; Myers, Umi; Welsh, Anthony, 1983-; Gandolfini, Michael, 1999-; Elswit, Robert, 1950-; et al. (Paramount, 2024)
Bob Marley was a musical and philosophical icon who inspired generations through his message of love and unity. Bob's story was one of overcoming adversity and revolutionary music.